Single face compaction on laboratory marshall specimen towards satisfactory degree of compaction and thickness - Haryati Yaacob,; Mohd Rosli Hainin,; Fung, Lung Chang (Universiti Kebangsaan Malaysia, 2014)
Investigation on the performance of bond strength between pavement layers has gain serious attention from researchers worldwide. Typical method to prepare the double layered testing specimen at laboratory scale is to follow the Marshall procedure or to perform coring on constructed field scale test lanes. For specimen prepared with Marshall procedure, binder course loose mix is compacted at double faces first prior to the application of wearing course loose mix in the compaction mould and perform the compaction of the loose wearing course later. This paper focused on the specimen prepared using Marshall procedure where the upper wearing course is subjected to single face compaction. The feasibility of single face compaction is investigated and the relevant amount of compaction blows is determined to achieve sufficient thickness and degree of compaction. Aggregate is proportioned to achieve a target thickness of 35, 50 and 65mm, at an allowable limit of ±1 mm. For the tested mix incorporating dense graded, open graded and gap graded mix, each mix managed to achieve the required degree of compaction at satisfactory thickness with respective compaction blows.